Implementasi program “AI untuk negeri” dalam penguatan literasi digital guru SMA Negeri 11 Muaro Jambi - Lely Mardiyanti; Eka Aghnia Syarif; Saparuddin Saparuddin; Ali Sadikin; Retni Sulistiyoning (STAI Auliaurrasyidin Tembilahan, 2025)
Rapid developments in artificial intelligence (AI) require educators to adapt to digital change so they can design learning experiences that remain relevant and grounded in real contexts. This community service program aims to strengthen teachers’ digital literacy through the implementation of the “AI for the Nation” initiative at SMA Negeri 11 Muaro Jambi. The program focuses on training teachers in prompt engineering as a foundational skill for using generative AI to develop teaching materials and assessments. The activities were carried out in three main stages: (1) preparation, which involved a needs analysis and the development of training materials based on real cases from the school environment; (2) implementation, conducted through a two-day interactive workshop covering key AI concepts in education, hands-on prompt design practice, and reflective discussion to build critical understanding; and (3) evaluation, carried out through observation of participant activities, assessment of their prompt outputs, and questionnaires to measure improvements in digital literacy. The results show a clear improvement in teachers’ understanding of basic AI concepts and their ability to design effective prompts. This program supports the development of educators’ digital competence and encourages the ethical, creative, and sustainable use of AI in teaching and learning.